Dietary Supplementation with Limnophila aromatica Extract on Growth Performance and Physiological Responses in Rana rugulosa - Wongtha, Surachai; Rattana, Khwanduean; Sangchanjiradet, Supavee; Dasri, Kajohnpong; Munglue, Phukphon (Journal of Food Health and Bioenvironmental Science, 2023)
This research was examined the effects of dietary Limnophila aromatica extract (LAE) on growth, intestinal histology, hematology and serum biochemistry of common lowland frog (Rana rugulosa). Frog (average initial weight 16.00±1.00 g) were fed with the diets supplemented with LAE at the concentrations of 0 (control), 1, 3 and 5% daily for 8 weeks. The qualitative test analysis for phytochemicals showed the presence of glycosides, steroids, alkaloids, flavonoids, phenolic compounds, saponins, terpenoids, coumarins and anthraquinones. After the feeding trial, frog fed different LAE diets significantly increased growth indices and feed conversion efficiency compared with the basal control (P<0.05). The survival rate did not differ among the groups (P>0.05). The improvement in intestinal morphology was observed in frog fed the diets containing LAE compared with the control (P<0.05). White blood cells were significantly decreased in frog fed 5% dietary LAE (P<0.05). There were no significant changes in red blood cells, hemoglobin, hematocrit, mean cell volume, mean cellular hemoglobin and mean cell hemoglobin concentration among the groups (P>0.05). Glucose, cholesterol, triglyceride, and alanine aminotransferase were significantly decreased in the treated frog compared with the control frog (P<0.05). Aspartate aminotransferase, alkaline phosphatase, uric acid, HDL-C, LDL-C, bilirubin-D, bilirubin-T and albumin were not affected by the diet supplementations (P>0.05). This study indicated that LAE supplementation produced a positive effect on growth, intestinal histomorphology and serum biochemistry in frog with the optimal level of 2.66%.